2013
DOI: 10.2147/ott.s44668
|View full text |Cite
|
Sign up to set email alerts
|

Circulating nucleic acids in plasma and serum (CNAPS): applications in oncology

Abstract: The presence of small amounts of circulating nucleic acids in plasma and serum (CNAPS) is not a new finding. The verification that such amounts are significantly increased in cancer patients, and that CNAPS might carry a variety of genetic and epigenetic alterations related to cancer development and progression, has aroused great interest in the scientific community in the last decades. Such alterations potentially reflect changes that occur during carcinogenesis, and include DNA mutations, loss of heterozygos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 154 publications
0
24
0
Order By: Relevance
“…So far >900 miRNAs have been discovered [28]. The mature miRNA with 20-24 nucleotides (nt) are produced from ~70 nt precursor RNA originated from long 300-5,000 base pair primary RNA.…”
Section: Epigenetics Modificationsmentioning
confidence: 99%
“…So far >900 miRNAs have been discovered [28]. The mature miRNA with 20-24 nucleotides (nt) are produced from ~70 nt precursor RNA originated from long 300-5,000 base pair primary RNA.…”
Section: Epigenetics Modificationsmentioning
confidence: 99%
“…The effectiveness of this approach has been demonstrated in different malignancies including breast, pancreatic and colorectal cancer (CRC)[1]. In the case of pancreatic cancer, liquid biopsy provides an advantageous technology regarding the anatomical and clinical difficulties for pancreatic tissue[2].…”
Section: Concept Of Liquid Biopsymentioning
confidence: 99%
“…It can be present in circulation in both protein-associated and free form[34]. Circulating mitDNA measurement and mutation analysis has been proposed to diagnose different malignancies such as breast tumors or epithelial ovarian cancer and hepatocellular or colorectal cancer, respectively[1,36]. …”
Section: Where Do Circulating Nucleic Acids Comes From and How Do Thementioning
confidence: 99%
See 1 more Smart Citation
“…The cfDNA in the plasma of cancer patients has been believed to contain circulating tumor DNA (ctDNA) for decades, although over ninety percent of cfDNA in healthy individuals is from metabolism of normal blood cells. Previous studies suggested that cfDNA can serve as a sensitive tool for early diagnosis of cancers [6][7][8][9][10] and the levels of ctDNA were reported to increase with the severity of cancers 11,12 . Currently, ctDNA is gradually recognized as a significant biomarker for cancer monitoring and treatment 3,5 , especially after several research groups reported the positive detection of ctDNA in early-stagy cancers [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%